Diagnostic Value of Serologic Tests in Celiac Screening - Saneian, Hosein (Medknow Publications & Media Pvt Ltd, 2012)
OBJECTIVES: Celiac disease is one of the malabsorption syndromes leads to growth and development retardation in children. There is no test lonely can definitely diagnose celiac; however, the collection of clinical findings, serologic tests, intestinal biopsy, and response to treatment may diagnose it. Although diagnostic value is variable in different studies, they are used a non-invasive and appropriate screening methods today. This study aimed to evaluate diagnostic value of celiac serologic tests in children less than 15-year-old. METHODS: During two years, this study conducted on children referred to Al-Zahra hospital (Isfahan, Iran). All the children who had duodenal biopsy tests were evaluated in terms of serologic tests and clinical symptoms due to suspected celiac. The results were analyzed through descriptive statistics, chi-square and Fisher's exact tests using SPSS software. RESULTS: 15.8 percent of children were under 2 years, 37.3 percent between age range of 2 to 12 years and 10.5 percent were above 12 years. 8.1 percent of children with negative anti-endomysial antibody (EMA) suffered from celiac; while 20.0 percent of children with positive EMA suffered from celiac. 15.4 percent of children with negative anti-gliadin antibody (AGA) had celiac; while 11.6 percent of those with positive AGA suffered from it. 11.1 percent of those with negative tissue transglutaminase antibody (tTG) and 37.5 percent with positive tTG suffered from celiac. CONCLUSIONS: According to our study results, there is no correlation between gastrointestinal symptoms such as vomiting diarrhea, anorexia, bulimia, and failure to thrive (FFT) with celiac. TTG was the best screening test method to diagnose celiac disease and other tests such as AGA and EMA do not have high diagnostic value.